2020
DOI: 10.1590/1678-4685-gmb-2019-0377
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic evidences of local thermal adaptation for the native fish Colossoma macropomum (Cuvier, 1818)

Abstract: Brazil has five climatically distinct regions, with an annual average temperature difference up to 14 ºC between the northern and southern extremes. Environmental variation of this magnitude can lead to new genetic patterns among farmed fish populations. Genetically differentiated populations of tambaqui (Colossoma macropomum Cuvier, 1818), an important freshwater fish for Brazilian continental aquaculture, may be associated with regional adaptation. In this study, we selected tambaquis raised in two thermally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Transcriptomic characterization of tambaqui exposed to (i) distinct climate change scenarios and (ii) during gonadal differentiation have provided a helpful resource for the understanding of the molecular mechanisms underlying both the adaptation to a future new climate and the process of sex determination [7,8,9]. Other molecular mechanisms related to enzymatic capacity for long-chain polyunsaturated fatty acid biosynthesis have also been confirmed by a functional characterization of core genes in these processes [10,11].…”
Section: Introductionmentioning
confidence: 95%
“…Transcriptomic characterization of tambaqui exposed to (i) distinct climate change scenarios and (ii) during gonadal differentiation have provided a helpful resource for the understanding of the molecular mechanisms underlying both the adaptation to a future new climate and the process of sex determination [7,8,9]. Other molecular mechanisms related to enzymatic capacity for long-chain polyunsaturated fatty acid biosynthesis have also been confirmed by a functional characterization of core genes in these processes [10,11].…”
Section: Introductionmentioning
confidence: 95%
“…The gene rbm39 was associated with prpf38b by co-expression in the STRING v11 database (Szklarczyk et al, 2019), and showed differential exon usage in response to thermal stress in our experiment. Furthermore, rbm39 was differentially expressed in one of two thermally distinct populations of tambaqui ( Colossoma macropomum ) and is thought to play a role in local adaptation to thermal conditions (Fé-Gonçalves et al, 2020). In spotted seabass ( Lateolabrax maculatus ), rbm39 was identified as a differentially expressed transcript in salt water versus fresh water (Tian et al, 2019), consistent with the differential exon usage identified in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The exposure of some species, particularly the Tambaqui (a model species), to climate rooms built to mimic the future scenario forecast by IPCC for the year 2050 revealed many damages and some degree of mortality to fish subjected to warmer temperatures. The whole transcriptome gene expression showed that differentially expressed genes act to readjust or adapt protein expression and respond to changes in their metabolism (Fé-Gonçalves et al 2020). Either they adjust their metabolism or die.…”
Section: Carbon Cycling and Storagementioning
confidence: 99%